MANAJEMEN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI MA KARYA BAKTI SUKASARI - Rusmana, Jajang; Ardiana, Lufi; Yuningsih, Yuyun; Yoseptry, Ricky (PENDIDIKAN SAINS DAN TEKNOLOGI, 2024)
This research aims to describe the management of school principals in improving teacher performance at MA Karya Bakti Sukasari. This can be seen in the implementation of school principal management in improving teacher performance, which includes planning, organizing, implementing, and supervising. This research uses a qualitative approach with descriptive research methods. The data sources used in this research used interview data collection techniques and documentation studies. Research data analysis was carried out through the following steps: (1) data reduction, (2) data presentation, (3) drawing conclusions. The results of the research show that: (1) The planning carried out by the head of MA Karya Bakti is based on the vision, mission, school goals, needs (need assessment) which are formulated in the school program created at the beginning of each new school year which is agreed upon with the teachers through meetings teachers' council; (2) The organization has been carried out by the school principal with the division of tasks according to the expertise of the teachers through new school year meetings; (3) The implementation of the school principal as a manager can be seen in the implementation of all programs that have been designed. This program is in accordance with the school program created at the beginning of each new school year as agreed with the teachers; and (4) Supervision carried out by the school principal to improve teacher performance, namely by conducting supervision. Supervision is carried out situationally, usually starting with student problems and then evaluating the teaching methods used by the teacher in class